Wideband continuous frequency tunable coaxial gyrotron oscillators - Dumbrajs, O.; Ioannidis, Z. C.; Tigelis, I. G. (Infrared and Millimeter Waves, 2007 and the 2007 15th International Conference on Terahertz Electronics. IRMMW-THz. Joint 32nd International Conference on, 2007)
We present the design of two continuous tunable CW coaxial cavity gyrotron oscillators, one of 330 GHz - 200 W with a bandwidth of 3 GHz for scientific applications and one of 30 GHz-150 kW with a bandwidth 0.4 GHz for industrial applications. The tuning of both gyrotrons is achieved by moving the tapered inner conductor in the axial direction and by adjusting the operating magnetic field.
Keywords: Bandwidth; bandwidth 0.4 GHz; bandwidth 3 GHz; coaxial cavity gyrotron oscillators; Coaxial components; Coaxial resonators; Frequency; frequency 30 GHz; frequency 330 GHz; Frequency tuning; Geometry; gyrotrons; magnetic field; microwave oscillators; microwave tubes; millimetre wave oscillators; millimetre wave tubes; Nuclear magnetic resonance; Oscillators; physics; power 150 kW; power 200 W; tapered inner conductor; tuning; Wideband; wideband continuous frequency tunable coaxial gyrotron oscillators